SISTEM PENDIDIKAN ISLAM PONDOK PESANTREN AL-FALAH BANJARBARU KALIMANTAN SELATAN (INTEGRASI SEKOLAH DAN PESANTREN) - Rafi'atun Najah Qomariah; Wa Muna; Mursyidatul Awaliyah (STIT Darul Hijrah Martapura, 2021)
Currently, the role of Islamic boarding schools (pesantren) is crucial in supporting social success. The importance of focusing on the education of students (santri) lies in its influence on their physical and emotional development. This study focuses on how Pondok Pesantren Al-Falah in Banjarbaru, South Kalimantan, integrates formal education with the traditional Islamic education system. Through a descriptive qualitative approach, the research reveals that Pondok Pesantren Al-Falah opts for a full integration model. This means that they fully maintain the characteristics and education system of the Salafiyah pesantren while ostensibly running two separate educational systems school and pesantren yet under the same foundation. The learning process at Pondok Pesantren Al-Falah adopts the regular school/madrasah format with a Madrasah Tsanawiyah (MTs) program for three years and a Madrasah Aliyah (MA) program for another three years, which is applied both in teaching at the pesantren and in the public school.